(untitled) (Research, Society and Development, 2024)
The organization of an industrial plant layout is a critical factor for both worker safety and production efficiency. In an industrial environment, neglecting space organization can lead to workplace accidents and operational inefficiencies. This article aims to present the development of a safe factory layout in an industry located in the Industrial Hub of Manaus, where the need to change the layout proved essential to meet safety standards and optimize production processes. The methodology followed structured steps: initial alignment with safety and production teams, mapping the current layout using AutoCAD software, developing the ideal layout, operational testing, and implementing changes. During the diagnosis, unsafe conditions and areas needing improvement were identified, such as narrow corridors and lack of signage. The new layout proposed widening the corridors and relocating pallets, in compliance with safety standards and optimizing space. The results showed a significant improvement in working conditions, with risk elimination and increased operational efficiency. The implementation was successful, and the adaptation of employees was quick, reinforcing the feasibility of collaborative interventions in the factory environment. Continuous layout review is essential to optimize safety and productivity, contributing to a safer and more efficient work environment, aligned with best industrial safety practices.